Cropland abandonment altered grassland ecosystem carbon storage and allocation and soil carbon stability in the Loess Hilly Region, China. (10th January 2020) - Xu, Hongwei; Wang, Xiukang; Qu, Qing; Zhai, Jiaying; Song, Yahui; Qiao, LeiLei; Liu, Guobin; Xue, Sha
Abstract: Determining changes in grassland ecosystem carbon (C) storage and soil C stability after cropland abandonment is important for estimating the regional C budget and global C cycle. However, the understanding of ecosystem C storage and allocation and soil C stability along the grassland restoration chronosequence is insufficient. Thus, grasslands with different recovery years (0, 2, 5, 8, 11, 15, 18, 26, and 30 years) were chosen to monitor the dynamics of grassland ecosystem C storage, vegetation biomass C storage, soil C storage, and soil C stability in different soil depths, as well as a natural grassland (NG) reference. The results showed that aboveground biomass (AGB), belowground biomass (BGB), soil C storage, ecosystem C storage, the very labile fraction of oxidizable C (C1) (0–0.3 m layers), the labile fraction of oxidizable C (C2) (0–0.3 m layers), and the C management index increased with the recovery years. The vegetation species richness (R), vegetation species evenness (E), and vegetation species diversity (H′) initially increased, peaking at 18a and then decreasing with recovery years, but the soil C stability index (SI) at 0–0.3 m decreased over time. Additionally, the AGB, BGB, litter biomass (LB), R, H′, ecosystem C storage, and SI (0–0.3 m and 0.5–1.0 m layers) of 30‐year grassland (GL30) showed no significant differences relative to those found in the NG. Furthermore, the soil C sequestration rate decreased with decreasing soil depth, while the soil C stability increased. These results suggest an optimistic outlook for the recovery of ecosystem C, but the soil C under these conditions is unstable, posing a risk to soil C sequestration in abandoned cropland on the Loess Plateau without appropriate management.